Memorandum of understanding between Universiti Teknologi MARA and Malaysia Automotive Robotics and IoT Institute / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2019)
The Malaysia Automotive Robotics and IoT Institute (MARii) has signed a Memorandum of Understanding with Universiti Teknologi MARA (UiTM) with the aim of strengthening, promoting and developing academic, cultural and research cooperation.